Neolithodes grimaldii A. Milne Edwards & Bouvier 1894 - Muñoz, Isabel; García-Isarch, Eva (Zenodo, 2013)
Neolithodes grimaldii (A. Milne Edwards & Bouvier, 1894) Lithodes Agasizii Smith, 1882: 8, pl. I, fig. 2 (in part, juveniles only); Smith, 1883: 25; Smith 1884a: 351; Smith, 1884b: 54; Smith, 1886: 34, pl. 3, figs. 1, 2 (not N. agassizii Smith, 1882). Lithodes agassizii.— Henderson, 1888: 42 (not L. agassizii Smith, 1882). Lithodes Grimaldii A. Milne Edwards & Bouvier, 1894a: 62, pl. 3; Heegaard, 1941: 13. Lithodes goodie Benedict, 1894: 479. Neolithodes Grimaldii. — A. Milne Edwards & Bouvier, 1894a: 92; A. Milne Edwards & Bouvier, 1894b: 120; Bouvier, 1895: 177; Bouvier, 1922: 36. Neolithodes grimaldii. — Squires, 1970: 111; Dawson & Yaldwyn, 1985: 101 (in list); Saint Laurent, 1985: 475 (in list); Macpherson, 1988a: 42, pls. 6, 7, figs 15B, 18; Pohle, 1990: 14; 140; Squires, 1990: 397, figs. 211, 212, pl. 10, 11; Türkay, 2001: 289 (list); He, 2005: 36; Felder et al ., 2009: 1069 (list); Ahyong, 2010: 73 (list); McLaughlin et al ., 2010: 12 (list). Material examined. Mauritania: MAURIT0811, stn 5, 21 °12.7'N, 18°45.4'E, 1699 m, 18.XI.2008, 1 ovigerous female, 173 × 158 mm (IEO-CD-MR08/761); MAURIT0811, stn 13, 20 °31.7'N, 18°03.3'E, 1835 m, 21.XI.2008, 1 ovigerous female, 152 × 147 mm (IEO-CD-MR08/762). Distribution. The species is distributed in northwestern and northeastern Atlantic waters. In the Eastern Atlantic, it presence has been reported in European waters, from Greenland and Iceland to the Bay of Biscay, and in the Canary and Cape Verde islands in the south, at 1267–3000 m (Macpherson 1988a). This material contributes with new records off West Africa, from Mauritanian waters, at depths between 1699 and 1835 m. Published as part of Muñoz, Isabel & García-Isarch, Eva, 2013, New occurrences of lithodid crabs (Crustacea: Decapoda: Lithodidae) from the coasts of Africa, with the description of a new species of Paralomis White, 1856, pp. 45-54 in Zootaxa 3670 (1) on page 47, DOI:10.11646/zootaxa.3670.1.3, http://zenodo.org/record/283929